Assessment the Impact of Asean Free Trade Area (AFTA) on Exports of Indonesian Agricultural Commodity - Heri Akhmadi (AGRARIS: Journal of Agribusiness and Rural Development Research, 2017)
This paper focuses on investigation whether Indonesian membership on ASEAN Free Trade Area (AFTA) increased export of agriculture commodity. The panel augmented gravity model data from 33 major partner countries over the period of 2000-2014 has been applied to analyze the factors affected Indonesian agricultural exports. The overall finding showed that Indonesian agricultural exports were positively correlated with the size of economy and partner countries population, while they are negatively correlated with the appreciation of currency exchange rate and the enrollment on free trade agreement. Moreover, the Indonesian membership on AFTA does not gave significant impact and profitable on Indonesian agricultural exports.